(untitled) (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2019)
Between 2005 and 2008 a research project about the deterioration causes of the petroglyphs of Campo Lameiro (Pontevedra) was developed. The substrate of the carvings was characterised as a two mica-granite, fine to medium grained, with granular allotriomorphic texture. Intense cracking is present in the rock at all levels, which is responsible of its high porosity and therefore its high capacity to absorb water. A dense network of diaclases was observed on site, however a specific study revealed that this does not involve a risk of massive loss of rock, which might affect the carved surfaces. The mineralogical and geochemical analysis showed that the granite was subjected to processes of hydrolysis and solubilisation-precipitation of iron, showing that water is the main deterioration agent in the lithic material.